Single phase flux switching DC linear actuator - Aravind, Chockalingam; I, Khumaira; Raja Othman, Raja Nor Firdaus Kashfi; Abdul Shukor, Fairul Azhar (2014)
A number of variable speed applications require linear actuation such as in linear compressors, drilling and cutting applications. In this research a flux switching DC induction actuator with a feedback sensor for operation in closed loop condition is proposed. The appropriate choice of the permanent magnet dimensions improves the performance of the PM machines. The linear induction actuator is chosen by the variations in the height to width of the permanent magnet through Finite Element Methods. Analysis on the effect of changing the magnet ratio on the torque and the cogging force is reported in this work. The flux switching between the adjacent poles is achieved through a control drive circuitry based on the feedback signal from the sensor. The static characteristic of such a machine is presented together with the experimental results.